Sharia-Compliant Deposit Insurance and Deposit Flows: Evidence from a Dual Banking Market - Putra Pamungkas; Laetitia Lepetit; Clovis Rugemintwari (Journal of Islamic Monetary Economics and Finance, 2025)
We investigate whether the introduction of Islamic Deposit Insurance (IDI) affects deposit flow of and the pricing by Islamic banks vis-à-vis conventional banks for the case of Indonesia. Using December 2014 announcement of a separate deposit insurance scheme for Indonesia’s Islamic and traditional banks into two different funds as an exogenous event, we employ a difference-in-differences (DID) framework using matched bank-level data from 18 Islamic and conventional banks, comparing periods before and after the policy announcement. Our findings indicate that the announcement significantly boosts the growth of small deposits in Islamic banks compared to traditional banks, with an apparent increase in deposit growth after separating deposit insurance funds.